Economic Consequences of Immigration to Austria - Sergej Vojtovic; M?gdaléna Tupá (Institute of Economic Research (IER), 2017)
Austria and low unemployment rate, higher salaries, more vacancies in comparison to the Slovak Republic together with the system of state benefits and geographical proximity have caused increased interest of Slovaks in work in the given country. The open asylum politics of Austria and Germany is attractive to immigrants from the third-world countries. Based on the analyses of development of work force emigration from the Slovak Republic and immigration to Austria, the study identifies migration trends in both countries. Calculations of migration benefits from the arrival of work force from the Central and East European countries and calculations of losses and benefits from the migration from the third-world countries aim at explaining the development of economical, social and demographic parameters in the country. Mathematic calculations of losses and benefits from migrations for a country and society are also introduced. These are based on the statistical data available from Eurostat, WTO, Statistical Office of the Slovak Republic, Statistic Austria, Ministry of Labour, Social Affairs and Family, World Bank, International Monetary Fund and data acquired from empirical surveys published in scientific publications. The study uses general scientific methods of induction, deduction, scientific abstraction and comparison, analysis and synthesis of selected facts, phenomena and processes. To calculate the data acquired, statistical and mathematical methods and calculations were implemented. The result of the experiment is to create a model approach to the evaluation of economic benefits and losses from work force migration from the Central and East European countries and, at the same time, immigration from the third-world countries. It may be stated that work force migration from Central and East Europe is beneficial for Austria. The study also shows expenses on immigrants while asylum procedures are taking place followed by expenses on their integration into the labor market and society.
Keywords: F22; 330; migration; migration management; labour migration; work force; target country; source country